If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2r = 2 Solving 4 + -2r = 2 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -2r = 2 + -4 Combine like terms: 4 + -4 = 0 0 + -2r = 2 + -4 -2r = 2 + -4 Combine like terms: 2 + -4 = -2 -2r = -2 Divide each side by '-2'. r = 1 Simplifying r = 1
| 6x:2*(1+2)=2 | | 5/7x+1=26 | | (l+3)(2w)=54 | | x^3+4x=60 | | -17n-14=-16n | | 4=x/6-4 | | 40x-10y=2370 | | 2w+(5+4w)=80 | | 10x-10y=2370 | | -1+4f=6f-7 | | 16-43=3(x-5)-3 | | -h-5=-18-11h+9h | | 12=55x | | 6+3p=-10+p | | 8/5x=85 | | -2-k=6-3k | | -7/2x=-21/10 | | x+7=4-x | | 5(n+2)+3/5(5+10n) | | -7(x+2)-12=36+1 | | -3g+5=-7-4-5g | | 10x^2+101x+10=0 | | 6-9j=-10j | | 2x+16=69 | | -9-7c=-4c+6 | | -3-3w=-4w | | 7(-2)+4(-10)= | | -4x=a | | -3-2s=-s-10 | | 2x(x+4)=9 | | 9x+1/2=38 | | -1/2x+8 |